Oxidant/antioxidant system markers and trace element levels in children with nutritional rickets - Dogan, Murat; Cesur, Yasar; Dogan, Sekibe Zehra; Kaba, Sultan; Bulan, Keziban; Cemek, Mustafa (WALTER DE GRUYTER GMBH, 2012)
Objective: To determine the oxidative stress and trace element levels in vivo in patients with nutritional rachitism associated with vitamin D deficiency. Materials and method: A total of 30 patients, 18 males and 12 females, were included in the study. Age, sex, medical history, vital, and physical examination findings of each patient documented at presentation were recorded. Serum calcium, phosphorus, alkaline phosphatase, parathormone, and 25-OH vitamin D levels, as well as oxidant and antioxidant system parameters and trace element levels were studied. After being diagnosed with rachitism, the patients were administered a single dose of 300,000 IU vitamin D by intramuscular injection. The same analyses were repeated post-treatment. Thirty children with normal anthropometric measurements were included as the control group. The analyses described above were performed only once for the control group. Results: Serum calcium, phosphorus, alkaline phosphatase, parathormone, and 25-OH vitamin D levels were different between the controls and children in the patient group (p<0.001). Analysis of trace element levels demonstrated markedly lower pretreatment zinc levels for the patient group compared to the controls, with a statistically significant difference (p=0.001). Comparison of pretreatment oxidant and antioxidant system markers between the patient and control groups demonstrated higher values for vitamin C, beta-carotene, reduced glutathione, and superoxide dismutase in the control group, whereas MDA was higher in the patient group. Conclusion: The present study demonstrated increased oxidative stress, reduced antioxidant defence system in patients with nutritional rachitism, with reduced oxidative stress and a pronounced improvement in the antioxidant system with vitamin D treatment.
Keywords: children; nutritional rickets; oxidant/antioxidant system; trace element levels; VITAMIN-D DEFICIENCY; OXIDATIVE STRESS; FREE-RADICALS; ZINC; SUPPLEMENTATION; GROWTH; D-3; EXPRESSION; CHILDHOOD; INCREASES; Endocrinology & Metabolism; Pediatrics